Japanese Speaking Anxiety in Kaiwa Classes: A Cross-Cohort Study of Japanese Language Education Students at UMY - Aisyah Nur Hajizah; Rosi Rosiah (Universitas Negeri Semarang, 2026)
This study examines speaking anxiety in Japanese kaiwa classes among students in a Japanese Language Education program at a private University in Yogyakarta. Since speaking is a central component of foreign language learning and is often associated with high levels of anxiety, the study investigates whether anxiety differs across student cohorts and identifies the factors contributing to it. Using a quantitative design, data were collected from 70 students drawn from four cohorts within a population of 113 students. The study employed a questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al., and the data were analyzed using SPSS. The findings indicate that students across all cohorts experienced a moderate level of speaking anxiety. However, the ANOVA results showed no statistically significant differences among cohorts, suggesting that academic level was not a determining factor in students’ speaking anxiwty. These findings indicate that speaking anxiety in Japanese language learning is shaped less by cohort membership than by individual and classroom-related factors, such as self-confidence, speaking experience, and perceived evaluation in classroom interaction.